Relation Between Voice Pleasantness and Distribution of the Spectral Energy - Varošanec-Škarić, Gordana (1999)
The aim of this paper is establishing the relation between the voice pleasantness and the relative energy in particular areas of spectrum. The results of the evaluation were correlated with acoustic variables based on the LTAS. The ANOVA was applied in order to determine the difference between subgroups (pleasant, average and unpleasant) according to the relative energy in particular spectrum areas. Male pleasant voices have significantly more relative energy in O-300 Hz and significantly less in 0.3- 0.55 kHz range and less than unpleasant voices in 0.55-0.65 kHz range. In the central spectrum ranges pleasant male voices have less relative energy than unpleasant voices, and in higher ranges they are similar to the average voices. Female pleasant voices don t differentiate significantly as male voices do. We can conclude that the distribution of energy in the spectrum has more influence on the evaluation of the male voice quality than on female voices.
Projekt MZOS
ENG